Return to play after UCL injury in gymnasts - Kemler, B. R.; Willier, D. P.; D`Amore, T.; Cohen, S. B.; Dodson, C. C.; Ciccotti, M. G. (The Physician and Sportsmedicine, 2024)
Background Injuries to the ulnar collateral ligament (UCL) are commonly reported in traditional overhead sports. Conversely, there is a lack of evidence outlining management and return to play (RTP) outcomes for gymnasts. This study aimed to evaluate RTP and patient reported outcomes (PROs) in gymnasts after operative and non-operative treatment of UCL injuries.